PERTANGGUNGJAWABAN KORPORASI DALAM PENYELESAIAN SENGKETA PERPAJAKAN (SUATU KAJIAN HUKUM DOKTRINAL) - Nindi Achid Arifki; Ilima Fitri Azmi (Politeknik STIA LAN Makassar, 2018)
This article attempts to explore deeply on the implementation of corporate accountability in Indonesia in tax dispute resolution. The implementation of corporate accountability in Indonesia is heavily influenced by working relations between manager, owner and corporation. These relations influence the scope of accountability of each form of corporation (with or without legal entity). The limited scope gives a particular consequence toward corporate legal action. Similar to corporate legal action in fulfilling tax duty, the legal subject arrangement as artificial person to represent any corporate legal action that is mentioned in private law concept, also specifically mentioned in Tax Regulation. The discourse on the issue is discussed using doctrinal law research method, by means of hermeneutic approach to translate the doctrine basis. It may be concluded that there is a doctrine of â€lifting the corporate veilâ€ related to the arrangement of corporate accountability in tax dispute resolution so that the selection of corporate law subject is seen from a wider perspective. Corporate accountability is not only limited to the management board but also includes stockholder and corporate leader.